Ibn al-Mu’tazz dan Teori al-Badī’; Pemikiran Balagah dalam Kritik Sastra Arab - Mohammad Yusuf Setyawan; Tatik Mariyatut Tasnimah (Universitas Muhammadiyah Gorontalo, 2022)
This article aims to describe the contribution of Ibn al-Mu'tazz in the development of Arabic literary criticism. Through his book entitled al-Badi>', Ibn al-Mu'tazz has succeeded in gathering the characteristics of the new school of thought promoted by Abu Tammam. Ibn al-Mu'tazz wanted to prove that the badi' arts that complied with Abu Tammam's poetry were previously known to the Arabs and are often found in the Qur'an, hadith, the sayings of companions, and in both classical and new poetry. According to Ibn al-Mu'tazz, badi' art includes 5 types, namely isti'a>rah, tajni>s, mutha>baqah, radd a'ja>z al-kala>m 'ala> ma> taqaddamaha>, and al-madzhab al-kala>mi>. In addition to discussing the five badi' arts, Ibn al-Mu'tazz also introduces what he calls muhasin al-kalam to provide greater benefits to the reader. Ibn al-Mu'tazz's contribution should be appreciated because for his services, the characteristics of the new school can be ascertained, making it easier for Arab critics in the next generation to make comparisons between the old school and the new school. As the founder of badi>' knowledge, Ibn al-Mu'tazz has made balagah as a medium in enriching literary criticism in his time.